Process Control: A Practical Approach - King, Myke (Wiley, 2016)
So why another book on process control?Process Control: A Practical Approachis a ground-breaking guide that provides everything needed to design and maintain process control applications.The book follows the hierarchy from basic control, through advanced regulatory control, up to and including multivariable control. It addresses many process-specific applications including those on fired heaters, compressors and distillation columns.Written with the practicing control engineer in mind, the book:Brings together proven design methods, many of which have never been published beforeFocuses on techniques that have an immediate practical applicationMinimizes the use of daunting mathematics – but for the more demanding reader, complex mathematical derivations are included at the end of each chapter Covers the use of all the algorithms, common to most distributed control systemsThis book raises the standard of what might be expected of even basic controls. In addition to the design methods it describes any shortcuts that can be taken and how to avoid common pitfalls. Proper application will result in significant improvements to process performance.Myke King’s practical approach addresses the needs of the process industry, and will improve the working practices of many control engineers.“This book would be of value to process control engineers in any country.”– Mr Andrew Ogden-Swift, Chairmain, Process Management and Control Subject Group, Institution of Chemical Engineers, UK“This book should take the process-control world by storm.”– Edward Dilley, Lecturer in Process Control, ESD Simulation Training